The Importance of Learning Pancasila and Citizenship in Instilling Ethics and Morality in Adolescent Students of SMAN 6 South Tangerang City - Marlina, Lina; Rahayu, Yayuk Muji (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aim of community service is to form students who are not only academically intelligent, but also have strong character, morals, and are aware of their responsibilities as citizens, especially students at SMAN 6 South Tangerang City. Problems are resolved in three activity stages, namely preparation, implementation and evaluation. Preparations were made by conducting a preliminary survey to see conditions in the field regarding students' attitudes and behavior towards the application of ethical values and morality. using lecture, discussion and question and answer methods, evaluation of activities is carried out for each stage by collecting and summarizing data from each stage of activity. The results of activities through socialization carried out by the community service team and continued with sharing information and experiences during discussion activities are 1) Students will have a clearer and deeper understanding of the values of Pancasila, such as justice, unity and humanity, as well as the importance of the role of they are good citizens. 2) The discussion will clarify how Pancasila is relevant to everyday life and how it is applied in various social situations. will help students not only understand the concepts of Pancasila and Citizenship, but also practice them in real life, both individually and in groups and for the output target in community service, it is planned to publish a journal in the community service journal.